236 FACTORS MODULATING P63 EXPRESSION IN CULTURED LIMBAL EPITHELIAL CELLS. (10th December 2015) - Salehi-Had, H.; Alvarenga, L. S.; Isseroff, R.; Schwab, I. R.
Abstract : Purpose: The expression pattern of p63, a homologue of the transcription factor p53, and whether it can be used as a corneal epithelial stem cell specific marker remain controversial. We investigated the p63 expression pattern in cultured limbal epithelial cells at different time points in culture, in sparse and confluent cultures, after growth factor starvation, and in single-cell-derived colonies. Methods: Harvested limbal epithelial cells were plated at 2.5 (sparse) or 5 (dense) × 104 cells/cm2 and evaluated for p63 expression at day 1, day 4, day 7, after starvation for 72hr, or in colonies derived from single cells. Expression of corneal lineage specific differentiation marker keratin 3 (K3) was correlated with p63 expression. Results were compared by one-way ANOVA. Results: More than 85% (85- 90%) of cells expressed p63 on Day 1 regardless of cell plating density. On day 4 while sparsely plated cultures were subconfluent and demonstrated high p63 expression (87.4%), densely plated cells were confluent and had markedly reduced p63 expression (16.9%). Starvation of subconfluent cultures arrested cell division yet did not decrease p63 expression. High p63 expressing cultures expressed low levels of K3 and this trend was reversed in confluent cultures. Most cells in all colonies derived from single cells expressed p63. Conclusions: The majority of corneal limbal epithelial cells express p63 in colonies derived from single cells and in subconfluent cultures regardless of time in culture or continuance of cell division. Cell-cell contact seems to be the main signal for decreasing p63 expression and inducing differentiation. It is likely that during times of rapid cell turnover, such as in subconfluent culture conditions, p63 is expressed by stem cells as well as transiently amplifying cells, while in quiescent confluent cultures which more closely mimicking in vivo conditions, p63 expression is more limited to the corneal epithelial stem cells.